2008
DOI: 10.1088/1742-6596/123/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Selection rule for turbulent structural formation: study of magnetized cylindrical plasmas

Abstract: Abstract. The three-field reduced fluid model was extended to describe the resistive drift wave turbulence in magnetized cylindrical plasmas. There include multiple energy exchange paths, and two kinds of nonlinear steady states were obtained in simulations with a fixed particle source: one with a zonal flow generated by modulational coupling of various unstable modes, which suppress transport, and the other with a streamer, which is a azimuthally-localized vortex structure and induces convective transport, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Nonlinear processes determine the oscillation frequency. It is found that a modification of the radial profile contributes to the variation of mode energy [32]. The oscillation occurs only when a small number of, but more than two, modes contribute to the formation of the turbulent structure.…”
Section: Nonlinear Simulationmentioning
confidence: 94%
“…Nonlinear processes determine the oscillation frequency. It is found that a modification of the radial profile contributes to the variation of mode energy [32]. The oscillation occurs only when a small number of, but more than two, modes contribute to the formation of the turbulent structure.…”
Section: Nonlinear Simulationmentioning
confidence: 94%